2020
DOI: 10.1002/bes2.1705
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inferred Gender on Patterns of Co‐Authorship in Ecology and Evolutionary Biology Publications

Abstract: Senior positions in academia such as tenured faculty and editorial positions often exhibit large gender imbalances across a broad range of research disciplines. The forces driving these imbalances have been the subject of extensive speculation and a more modest body of research. Given the central role publications play in determining individual outcomes and progress in academic settings, unequal patterns of authorship across gender could be a potent driver of observed gender imbalance in academia. Here, we inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 48 publications
(49 reference statements)
1
14
0
1
Order By: Relevance
“…If the author position on papers in our dataset varied by gender [ 45 ], then it could bias interpretations about collaboration behaviour and career progression. Therefore, we checked whether female and male focal authors differed in their proportion of either first or last author papers, after accounting for the first publication year, given that number of authors on publications has increased with time [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…If the author position on papers in our dataset varied by gender [ 45 ], then it could bias interpretations about collaboration behaviour and career progression. Therefore, we checked whether female and male focal authors differed in their proportion of either first or last author papers, after accounting for the first publication year, given that number of authors on publications has increased with time [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…The effects of gender or inferred gender with respect to male bias and privilege can also be observed in relation to the coauthoring of academic research, with the study by Frances et al (2020) finding that within the field of biology, male researchers in the last author position were more likely to co-author with other males, whereas women first and last authors were more likely to publish with men. Furthermore they found that the proportion of women co-authors on papers remained well below the proportion of PhDs awarded to women in biology over the same time period for their research.…”
Section: The Practices That Prevail Todaymentioning
confidence: 98%
“…Systems of patriarchy vary in their manifestation and severity globally, but are pervasive and have infiltrated all levels of society including scientific research (Haghighat-Sordellini 2010; Golash-Boza et al 2019; Uchendu and Edeagu 2021; Kocabıçak 2022). While self-identified women are not excluded from the field of biology as a whole, they are often excluded from prestigious tenured and editorial positions as well as collaboration networks (West et al 2013; Frances et al 2020; Madzima and MacIntosh 2021; Lerman et al 2022). Studies suggest that gender biases exist in hiring, publication, and funding decisions (Larivière et al 2013; Fox et al 2016; Bonham and Stefan 2017; Holman et al 2018; Witteman et al 2019; Frances et al 2020; Wapman et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…While self-identified women are not excluded from the field of biology as a whole, they are often excluded from prestigious tenured and editorial positions as well as collaboration networks (West et al 2013; Frances et al 2020; Madzima and MacIntosh 2021; Lerman et al 2022). Studies suggest that gender biases exist in hiring, publication, and funding decisions (Larivière et al 2013; Fox et al 2016; Bonham and Stefan 2017; Holman et al 2018; Witteman et al 2019; Frances et al 2020; Wapman et al 2022). These inequities impact academic currency on job and funding markets and further exacerbate gender imbalances in academia.…”
Section: Introductionmentioning
confidence: 99%